Tourism Experiential Learning through Academic Field Trips in Higher Education. Copper Canyon (Mexico) - González Herrera, Manuel Ramón (2021)
Th e professionalization of tourism education through experiential learning by fi eldwork should be a key aspect of sustainable tourism development strategies. Based on the previous statement, the aim of this research is to develop a tourism learning experience through an academic fi eld trip in Copper Canyon, with the purpose of generating a practical learning situation that serves as a strategy and practice of sustainability in the syllabus of Tourism Planning at the Autonomous University of Ciudad Juarez. An experimental methodology was implemented with students (n=26) from the advanced level of the tourism program that participated in the fi eld trip, and mixed methods of empirical and theoretical types were applied. During the practical activity, the geospatial approach was applied to the study of the destination by interpreting the production process of the tourism space, as well as, the recognition of the tourism model, the inventory and assessment of tourist resources, and the analysis of impacts. Th e results allowed for comprehension and justifi cation of the contribution of the practical learning process to the formation of tourism knowledge, by incorporating fi eld trips to develop experiences through practical learning.